The effect of minimum wages on the employment and earnings of South Africa's domestic service workers - Tom Hertz (W.E. Upjohn Institute for Employment Research, 2005)
Minimum wages have been in place for South Africa's one million domestic service workers since November of 2002. Using data from seven waves of the Labour Force Survey, this paper documents that the real wages, average monthly earnings, and total earnings of all employed domestic workers have risen since the regulations came into effect, while hours of work per week and employment have fallen. Each of these outcomes can be linked econometrically to the arrival of the minimum wage regulations. The overall estimated elasticities suggest that the regulations should have reduced poverty somewhat for domestic workers, although this last conclusion is the least robust.
Keywords: 330; Mindestlohn; Hauspersonal; Beschäftigung; Einkommen; Südafrika